2017
DOI: 10.1103/physrevb.96.144421
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of spin pumping and spin transfer torque upon Ni81Fe19 thickness in Ta/Ag/Ni81

Abstract: Spin pumping has been studied within Ta/Ag/Ni 81 Fe 19 (0-5 nm)/Ag(6 nm)/Co 2 MnGe(5 nm)/Ag/Ta large-area spin valve structures, and the transverse spin current absorption of Ni 81 Fe 19 sink layers of different thickness has been explored. In some circumstances the spin current absorption can be inferred from the modification of the Co 2 MnGe source layer damping in vector network analyser ferromagnetic resonance (VNA-FMR) experiments. However the spin current absorption is more accurately determined from ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…We focus our discussion on the spin mixing conductance of layer i, (g ↑↓ i ) related to the dimensionless spin pumping parameter η ij . In particular it has been shown that the real part of g ↑↓ i relates to η ij as [39] R(…”
Section: Introductionmentioning
confidence: 99%
“…We focus our discussion on the spin mixing conductance of layer i, (g ↑↓ i ) related to the dimensionless spin pumping parameter η ij . In particular it has been shown that the real part of g ↑↓ i relates to η ij as [39] R(…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental techniques that offer these capabilities are lacking. X-ray detected ferromagnetic resonance (XFMR) with circularly polarized x-rays, i.e., dynamic x-ray magnetic circular dichroism (XMCD) [11][12][13], has proven an indispensable tool in the investigations of spin dynamics in magnetic multilayers [7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26]. By combining the capabilities of ferromagnetic resonance (FMR) and x-ray absorption spectroscopy as the underlying characterization mechanism, dynamic XMCD can probe magnetic precessions with element specificity, valence state sensitivity, and phase resolution.…”
mentioning
confidence: 99%
“…By combining the capabilities of ferromagnetic resonance (FMR) and x-ray absorption spectroscopy as the underlying characterization mechanism, dynamic XMCD can probe magnetic precessions with element specificity, valence state sensitivity, and phase resolution. XFMR has enabled the determination of effective spin mixing conductance of a spin valve with multiple spin sink layers [26], resolving interlayer anisotropic Gilbert damping effects in magnetic source and sink layers coupled by spin pumping [24], and the detection of coherent AC spin current propagation through antiferromagnetic CoO [7] and NiO [8]. Analogous to its static counterpart, dynamic XMCD is sensitive to ferromagnetic order and probes the net vector sum of magnetic moments associated with a certain element or ion.…”
mentioning
confidence: 99%
“…However, for asymmetric system similar to the present case, where FM1 and FM2 are designed with different intrinsic parameters (uniaxial and cubic anisotropy, shape anisotropy, saturation magnetization), spin pumping is to be analyzed as a nonreciprocal process with dissimilar values of gFM1FM2 and gFM2FM1 for the different material interface on each side of the insertion layer . However, a simplified approximation that gFM1FM2=gFM2FM1=g is also debated in the literature . In this comprehensive study, we performed field‐sweep broadband ferromagnetic resonance (FMR) measurements using vector network analyzer (VNA) to analyze spin‐pumping in soft magnetic and asymmetric Fe 50 Pt 50 /Cu/Fe 20 Ni 80 trilayer structure.…”
mentioning
confidence: 99%
“…Following the practice for other frequencies, the extracted ΔH values are plotted as a function of f for Fe 50 Pt 50 and Fe 20 Ni 80 in Figure c,d respectively. From the slope of anticipated linear dependence, we calculated the effective damping parameter αeff= α0+normalα using μnormaloΔH=μnormaloΔHnormalo+2πγαefff, where the reference value of γFe50Pt50 = 29.5 GHz T −1 and γFe20Ni80= 29.5 GHz T −1 is considered from literature . Noticeable enhancement in damping parameter αeff = 0.015 ± 0.001 and 0.031 ± 0.001 is obtained for Fe 20 Ni 80 and Fe 50 Pt 50 , respectively, in multilayer sample attributed to spin‐pumping effect, while uncapped samples Si/Fe 20 Ni 80 and Si/Fe 50 Pt 50 exhibited smaller values of α °, to be 0.0059 ± 0.0003 and 0.0228 ± 0.0006, respectively .…”
mentioning
confidence: 99%